2009
DOI: 10.1577/m08-210.1
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a Probabilistic Sampling Design to Determine Bull Trout Population Status Using Redd Counts in Basins of the Columbia River Plateau

Abstract: Redd counts are commonly used to monitor the current population status, trends in abundance, and distribution of bull trout Salvelinus confluentus. In many cases redd counts are conducted at subjectively selected sites, and there has been limited evaluation of statistical sampling designs. We evaluated the utility of the generalized random tessellation stratified (GRTS) sampling design to determine bull trout population status through redd counts. We tested a sampling effort that would be economically practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
(34 reference statements)
2
12
0
Order By: Relevance
“…For example, it has been used to determine bull trout (Salvelinus confluentus) population status through counts in basins of the Columbia River Plateau in the USA (Jacobs et al, 2009) and to develop ArcGIS tools via a forest biodiversity survey in a case study in Hunan Province, China (Li et al, 2012). Here, we illustrate the use of GRTS, and provide a comparison with StRS for bivalve surveys.…”
Section: Monitoring Surveys: Classical Methodology and New Approachmentioning
confidence: 99%
“…For example, it has been used to determine bull trout (Salvelinus confluentus) population status through counts in basins of the Columbia River Plateau in the USA (Jacobs et al, 2009) and to develop ArcGIS tools via a forest biodiversity survey in a case study in Hunan Province, China (Li et al, 2012). Here, we illustrate the use of GRTS, and provide a comparison with StRS for bivalve surveys.…”
Section: Monitoring Surveys: Classical Methodology and New Approachmentioning
confidence: 99%
“…At low redd abundance none of their sampling designs were accurate. In a GRTS sampling design for bull trout in the Columbia Basin, Jacobs et al (2009) found that accuracy ranged from 15 percent to 35 percent and was dependent on redd distributions within basins and that there was no reduction in accuracy with sample sizes between 10 and 50 sites. Our results are similar in that increased sample size appears to only marginally improve the precision of our estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Redd surveys occurred weekly from mid-September through early November for fall Chinook salmon, and every 2 weeks from early March through late May for winter steelhead. During each foot survey, newly identified redds were flagged and georeferenced using recreationalgrade global positioning system (GPS) units (Courbois et al 2008;Jacobs et al 2009). The reported accuracies from the GPS units generally ranged from 2 to 15 m. In subsequent surveys, previously flagged redds were inspected to determine whether they should be classified as "still visible" or "not visible".…”
Section: Datamentioning
confidence: 99%
“…This methodology allowed us to track the new redds and all visible redds in each survey. The individual redd coordinates were assembled into a geographic information system (GIS) database (Isaak and Thurow 2006;Jacobs et al 2009). GPS points were moved to the closest point on the 1 : 24 000 stream layer, except in cases where the coordinate was clearly in error owing to poor satellite coverage.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation